Synthesis of Secondary and Tertiary Alkyl Boronic Esters by gem‐Carboborylation: Carbonyl Compounds as Bis(electrophile) Equivalents. Issue 32 (12th July 2018) - Shi, Dunfa; Wang, Lu; Xia, Chungu; Liu, Chao
Abstract: An unprecedent gem ‐carboborylation of aldehydes and ketones provides access to various secondary and tertiary alkyl boronic esters. The addition of B2 pin2 to a carbonyl compound generates α‐oxyl‐substituted alkyl boron species. Organolithium and Grignard reagents are then applied as C nucleophiles for the 1, 2‐metalate rearrangement process. The organolithium reagents can also be generated by C−H lithiation or halogen/lithium exchange. The use of chiral ligands led to the generation of chiral alkyl boronic esters in enantioenriched form, demonstrating that the enantioselectivity of this transformation is catalyst‐controlled. Abstract : One electrophile, two nucleophiles : The gem ‐carboborylation of aldehydes and ketones generates various secondary and tertiary alkyl boronic esters. The addition of B2 pin2 to the carbonyl group provides an alkyl boronate with an α‐leaving group, which undergoes a 1, 2‐metalate rearrangement upon addition of an organolithium or Grignard reagent.